First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations The PEOPLE'S LEAGUE of HEALTH Patron: HIS MAJESTY THE KING FOUNDED IN 1917 BY MISS OLGA NETHERSOLE, R.R.C. Vice Presidents: THE LORD BISHOP OF BIRMINGHAM THE RIGHT HON. VISCOUNT BURNHAM SIR STEPHENSON KENT. K.C.B THE RIGHT HON. LORD LEVERHULME THE RIGHT HON. SIR FREDERICK MILNER Bart. THE MARCHIONESS OF BAERDEEN AND TEMAIR THE RIGHT HON. VISCOUNT NORTHCLIFFE SIR BASIL ZAHAROFF, G.C.B., G.B.E. Hon. Organiser: MISS OLGA NETHERSOLE. R.R.C. Appeal Director: THE COUNTESS CURZON OF KEDLESTON Hon. Secretary: LT.-COL. J.A. INNES, D.S.O. Hon. Treasurer: THE HON. FRANCIS N. CURZON MEDICAL COUNCIL. PROF. J.G. ADAMI, C.B.E, M.D., F.R.S., ETC., Vice-Chancellor of Liverpool University. RT. HON. SIR CLIFFORD ALLBUTT, K.C.B., M.D., F.R.S. [ETC. SIR ROBERT ARMSTRONG-JONES, M.D. SIR HARRY BALDWIN, L.D.S., M.R.C.S. SIR GILBERT BARLING, Bart., K.B.E., M.D., F.R.C.S. LADY BARRETT, C.B.E., M.D., M.S., B.Sc. NORMAN BENNETT, M.A., M.B., B.C.Cantab., L.D.S. C.J. BOND, C.M.G., F.R.C.S SIR BRUCE BRUCE-PORTER, K.B.E., C.M.G., M.D. CHARLES BUTTAR, M.A., M.D. FARQUHAR BUZZARD, M.D., F.R.C.P. ERNEST CLARKE, M.D., F.R.C.S. PROF EDGAR L. COLLIS, M.D., M.R.C.P. SIR ANDERSON CRITCHETT, BART. K.C.V.O., F.R.C.S. COLONEL S. LYLE CUMMINS, C.B., C.M.G., LL.D., M.D., LT-COL. F.E. FREMANTLE, M.P., M.A., F.R.C.P., D.P.H. SIR ALFRED D. FRIPP, K.C.V.O., C.B., M.S., F.R.C.S ARTHUR GILES, M.D., B.Sc., F.R.C.S. COLONEL L. W. HARRISON, D.S.O., R.A.M.C. LEONARD HILL, M.D., F.R.S. EDWARD, O.B.E., M.D., D.P.H. MONTAGU HOPSON. L.D.S. MAJOR-GEN. SIR ROBERT JONES, K.B.E., C.B., F.R.C.S. A. F. STANLEY KENT, M.D., D.Sc. PROF H.R. KENWOOD, C.M.G, F.R.S.E, D.P.H. JANET LANE-CLAYPON, M.D., J.P. ARTHUR LATHAM, M.D., F.R.C.P. SIR JAMES MACKENZIE, M.D., F.R.C.P., .U.D., F.R.S. SIR LESLIE MACKENZIE, M.A., LL.D., M.D., F.R.C.P. EWEN J. MACLEAN, M.D., M.R.C.P. OTTO MAY, M.A., M.D., PROFESSOR E.J. MCWEENEY, M.D., F.R.C.P. C. KILLICK MILLARD, M.D., D.Sc., M.O.H, LEICESTER BENJAMIN MOORE, D.Sc., F.R.S. SIR MALCOLM MORRIS, K.C.V.O., F.R.C.S. (Ed.) SIR FREDERICK MOTT, K.B.E., M.D., F.R.S., F.R.C.P. SIR BERKELEY MOYNIHAN, K.C.M.G., C.B., M.S., F.R.C.S. SIR THOMAS OLIVER, M.D., LL.D., F.R.C.P., Professor of Medicine in the University of Durham. LEWIN PAYNE, L.D.S., M.R.C.S., L.R.C.P. SIR ROBERT PHILIP, M.A., M.D., F.R.C.P., F.R.S. HUGH PLAYFAIR, M.D., F.R.C.P. F.R.C.S. W.A. POTTS, M.A., M.D. ERIC PRITCHARD, M.A., M.D., M.R.C.P. SIR MILSON REES, C.V.O., F.R.C.S. (ED.) SIR ARCHDALL REID, K.B.E., M.B., C.M. LT-COL. SIR HUGH RIGBY, K.C.V.O., M.S., F.R.C.S. SIR HUMPHREY ROLLESTON, K.C.B., M.D., F.R.C.P. C.W. SALEBY, M.D., F.R.S.(Ed.), Chairman, National Birth Rate Commission MRS. SCHARLIEB, C.B.E., M.D., M.S., J.P. FRANK SHUFFLEBOTHAM, M.A., M.D., M.R.C.P. E.H. STANCOMB, M.B., C.M. W.C. SULLIVAN, M.D., B.C.H., B.A.O. MISS BARBARA TCHAVKOVSKY, M.D. SIR JOHN LYNN THOMAS, K.B.E., C.M.G., F.R.C.S. HUNTER TOD, M.A., M.D., F.R.C.S. E.B. TURNER, F.R.C.S. MISS JANE WALKER, M.D., J.P. R. MCNAIR WILSON. M.B., Ch.B. SIR GERMAN SIMS WOODHEAD, K.B.E., LL.D., M.D., F.R.C.P. LAY COUNCIL. MISS M.S. ALLEN, O.B.E., Commandant, Women Auxiliary [Service J. AMES, Industrial League and Council MRS. ARCHDALE, Women's Industrial League Lady BADEN-POWELL, Commissioner of Girl Guides SIR ROBERT BADEN-POWELL, Bart. K.C.B., K.C.V.O., F.R.G.S., Chief Scout WILLIAM BAKER, Dr. Barnado's Homes MISS LILLIAN BARKER, O.B.E., Ministry of Labour THE LORD BISHOP OF BIRMINGHAM C.W. BOWERMAN, M.P., Sec., Parliamentary Committee, Trades Union Congress LORD WILLOUGHBY DE BROKE THE RIGHT HON. LADY BYRON, D.B.E. MRS. CAMERON-SWAN, Industrial Welfare Society LORD CHARNWOOD RIGHT HON. J.R. CLYNES, M.P. MISS DAMER DAWSON, D.B.E. LADY DENMAN, President, Federation of Women's Institutes MRS. OGILVIE GORDON, D.Sc. Ph.D., National Council of Women of Great Britain and Ireland WILLIAM CLARKE HALL, Chairman of the Juvenile Courts DR. C.W. KIMMINS, M.A., D.Sc. SIR JOHN KIRK, Ragged School Union CAPTAIN H. DE WINTON KITCAT, R.N., O.B.E., Waifs and Strays Society SIR JOHN MACALISTER, F.S.A., F.R.G.S. MISS MCWILLIAM, Y.W.C.A., M.B.E. MISS NORAH MARCH, D.Sc., M.R.SAN.I. HENRY MILL, SEC, National Sunday League MISS M. NORRINGTON, Workers' Educational Association SIR ARTHUR PEARSON, Bart., C.B.E. A. PUGH, Iron and Steel Trades Confederation SIR ROBERY HENRY REW, K.C.B., President, Associated Village Clubs DAME FLORENCE SIMPSON, D.B.E., Q.M.W.A.A.C. CAPT. D. SIMSON, British Legion LADY HENRY SOMERSET THE HON. SIR ARTHUR STANLEY, G.B.E., C.B., M.V.O. REAR-ADMIRAL SIR HARRY H. STILEMAN, K.B.E., Hon. Director Dr. Barnardo's Homes MISS JULIA VARLEY, Organiser, Workers' Union SIR SAMUEL WARING, BART. MISS J.F. WOOD, B.A., President, N.U.T. SIR ARTHUR YAPP, K.B.E., Y.M.C.A. Finance Committee: SIR GILBERT GARNSEY (Price, Waterhouse & Co.) SIR EDWARD HULTON, Bart. H.S. LAMBERT, Treasurer King George's Pension Fund for Actors and Actresses. Recreation and Entertainment Committee HENRY AINLEY SIR JOHNSTON FORBES-ROBERTSON LORD LONSDALE LADY ALEXANDER MRS. LIONEL HARRIS SIR GERALD du MAURIER VISCOUNTESS BARRINGTON SIR JOHN AND LADY MARTIN-HARVEY DAME NELLIE MELBA D.B.E. SIR FRANK BENSON LADY KENT THE HON. MRS. GRAHAM MURRAY MISS GLADYS COOPER THE HON. MRS. LAUNCELOT LOWTHER LADY WYNDHAM Propaganda Committee: SOLOMON J. SOLOMON, R.A. H.G. WELLS Liaison Committee with the Ministry of Health: SIR BRUCE BRUCE-PORTER K.B.E., C.M.G., M.D., Chairman. SIR ALFRED FRIPP, K.C.V.O., C.B., M.S, F.R.C.S. DR. BUTTAR SIR HARRY BALDWIN, L.D.S., M.R.C.S. MISS OLGA NETHERSOLE, R.R.C. Hon. Solicitors: MESSRS. FLADGATE & CO., 18, Pall Mall, S.W. Hon. Auditors: EDWARD MOORE & SON, Thames House, Queen Street Place, E.C. Bankers: LONDON COUNTY WESTMINSTER & PARR'S BANK 200/B/3/2/C693/1/71